The predictive validity of the post-conviction risk assessment among federal offenders - Luallen, Jeremy (Criminal justice and behavior, 2016)
In the U.S. federal court system, the Probation and Pretrial Services Office (PPSO) uses a tool known as the Post-Conviction Risk Assessment (PCRA) to assess offender risk and identify challenges offenders face while under supervision. This article evaluates the PCRA and its components to determine its usefulness as a predictive tool for evaluating risk. Overall, we find that the PCRA is an effective tool for classifying offenders as it is currently designed, achieving a level of predictive validity comparable with its competitors. Notably, we also find that the PCRA effectively differentiates offenders early in supervision terms, and that its predictive power diminishes as time under supervision lengthens. Finally, the strength of PCRA classification appears to vary with offense type. The PCRA performs well for some offenses including drug, violent, and property offenses, but provides less utility in reliably predicting less common offenses.